Risk factors associated with secondary displacement in fractures of the humeral greater tuberosity - Chen, Qing-Quan; Chen, Han-Lin; Wang, Hong-Shen; Huang, Xiao-Li; Chen, Jin-Shui; Yang, Xiu (Frontiers in Surgery, 2025)
BackgroundThe incidence of secondary displacement in fractures of the greater tuberosity of the humerus remains high, irrespective of whether conservative or surgical treatment is administered. However, the specific risk factors contributing to secondary displacement of the greater tuberosity of the humerus have not been previously reported. The primary objective of this study was to analyze the risk factors associated with secondary displacement of the greater tuberosity of the humerus and to summarize corresponding guidelines for clinical diagnosis and treatment.MethodsA retrospective analysis was conducted on patients with fractures of the greater tuberosity of the humerus who received treatment at the same trauma center between January 2018 and December 2022. The following variables were recorded for each patient: age, gender, injured limb (left/right), whether the fracture was comminuted, bone density, fracture displacement, shoulder joint dislocation, treatment plan, and treatment outcomes, including the success rate of reduction and the time of secondary displacement. The patients were categorized into two groups based on the absence or presence of secondary displacement. For statistical analysis, the Mann–Whitney U test and logistic regression analysis were employed. The significance level was set at P < 0.05.ResultsAmong the 177 patients enrolled in this study, 144 (81.36%) did not exhibit secondary displacement, while 33 (18.64%) did present with such displacement. Significant statistical differences were observed between the two groups in mean age, fracture type, bone mineral density, shoulder dislocation, and reduction quality of fracture, indicating a statistically significant association (P < 0.05). However, no significant difference was found in gender, Left/right limbs, displacement of fracture, and treatment method (P > 0.05). Logistic regression analysis revealed that comminuted fractures, osteoporosis, shoulder dislocation and poor reduction independently contributed to an increased risk of secondary displacement of the greater tuberosity of humerus.ConclusionsComminuted fracture, osteoporosis, shoulder dislocation, and poor reduction have been identified as independent risk factors for secondary displacement. In the course of clinical diagnosis and treatment, it is imperative to consider the potential adverse prognosis that may be associated with these conditions.